Bears and Pipeline Construction in Alaska - Follmann, Erich H.; Hechtel, John L. (ARCTIC, 1990)
Serious problems were encountered with bears during construction of the 1274-km-long trans-Alaska oil pipeline between Prudhoe Bay and Valdez. This multi-billion dollar project traversed both black bear (Ursus americanus Pallas) and grizzly bear (U. arctos L.) habitat throughout its entire length. Plans for dealing with anticipated problems with bears were often inadequate. Most (71%) problems occurred north of the Yukon River in a previously roadless wilderness where inadequate refuse disposal and widespread animal feeding created dangerous situations. Of the 192 officially reported bear problems associated with the Trans-Alaska Pipeline System (TAPS)(1971-79), about 65% involved the presence of bears in camps or dumps, 13% the feeding of bears on garbage or handouts, 10% property damage or economic loss, 7% bears under and in buildings, and only 5% charges by bears. Remarkably, no bear-related injuries were reported, suggesting that bears became accustomed to people and did not regard them as a threat. Following construction of the TAPS there have been proposals for pipelines to transport natural gas from Prudhoe Bay to southern and Pacific-rim markets. Based on past experience, some animal control measures were developed during the planning phase for the authorized gas pipeline route in Alaska. Fences installed around 100-person "survey" camps were found to be effective in deterring bears in two traditionally troublesome areas.